Insight into the complex regulation of CD133 in glioma - Campos, Benito; Herold-Mende, Christel (International journal of cancer, 2011)
The transmembrane protein CD133 and its extracellular epitope AC133 are controversial cancer markers. In glioma, AC133 demarcates a subpopulation of stem-like tumor cells, so-called cancer stem cells (CSCs), which seem to drive tumor formation and are highly resistant to conventional chemo- and radiotherapy. Lately, experimental evidence for the existence of AC133-independent CSCs has challenged the importance previously attributed to AC133-positive glioma cells. These findings either imply that (i) AC133-positive and AC133-negative glioma cells comprise different, independent CSC populations, (ii) AC133-positive glioma cells are derived from primordial AC133-negative CSCs or (iii) AC133-negative CSCs have lost AC133 expression, while retaining their stem-like features and tumor initiation capacity, and can reacquire AC133 expression in vivo. In our article, we review evidence for and against each of the possible tumor models in glioma and will discuss technical hurdles in the AC133 detection process. In addition, we will outline new insights into CD133 regulation, which suggest certain degree of plasticity between some AC133-positive and AC133-negative CSC populations.
Online 17 Sep2010
Gesehen am 27.06.2022